The Use of GaMALaMA App to Improve Earthquake Disaster Mitigation Awareness in Islamic Junior High Schools - Saprudin Saprudin; Rahim Achmad; Fatma Hamid; Rohima Wahyu Ningrum; Salkin Lutfi; Marwis Aswan (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
The integration of mobile-based gamification applications in education is crucial for enhancing student engagement and learning outcomes. This study analyzed the effectiveness of the GaMALaMA application, a mobile gamification tool, in improving students’ earthquake disaster mitigation awareness (EDMA) in Islamic junior high schools. An experimental research design with a pretest-posttest control group approach was employed, involving 55 students from a state Madrasah Tsanawiyah (MTs) in Ternate City, Indonesia. The results showed a significant improvement in EDMA among students who used the GaMALaMA app in addition to science textbooks compared to those who used only textbooks. This improvement was attributed to the incorporation of game design elements, such as points, challenges, levels, time constraints, rules, and leaderboards, which stimulated student engagement and supported independent learning beyond the classroom. The experimental group showed a high level of EDMA improvement (<g> = 0.76), while the control group showed a medium level (<g> = 0.64). These findings suggest that mobile-based gamification can enhance science learning in Islamic junior high schools. The study highlights the importance of teacher and parent cooperation in supporting students’ use of gamification apps for independent learning outside school hours.